2017
DOI: 10.1002/jcb.26205
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of MicroRNAs in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis is one of the most common types of inflammatory joint diseases. Women, smokers, and people with positive family history are more susceptible to this disease. Diagnostic criteria include at least one swollen joint that has not been caused by other diseases. MicroRNAs are non-coding RNAs that are evolutionarily conserved and have a length of 18-25 nucleotides. MicroRNAs control gene expression at the post-transcriptional level via promoting mRNA degradation or translational repression. Recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 80 publications
0
56
0
Order By: Relevance
“…2 The management of RA is limited to retarding the progression of the disease, improving functional capacity, and relieving pain. With regard to RA, miRNAs may serve as potential biomarkers for both diagnosis and prognosis for RA, 5 with, in particular, evidence for miR-146a/b upregulation in RA synovial tissue, 6 and miR-125 upregulation in peripheral blood mononuclear cells and plasma posttreatment. 3 miRNAs are a class of endogenous, single-stranded, noncoding RNAs with about 22 nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…2 The management of RA is limited to retarding the progression of the disease, improving functional capacity, and relieving pain. With regard to RA, miRNAs may serve as potential biomarkers for both diagnosis and prognosis for RA, 5 with, in particular, evidence for miR-146a/b upregulation in RA synovial tissue, 6 and miR-125 upregulation in peripheral blood mononuclear cells and plasma posttreatment. 3 miRNAs are a class of endogenous, single-stranded, noncoding RNAs with about 22 nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating publications have suggested aberrantly expressed or dysfunctional miRNAs may serve as novel biomarkers for rheumatic diseases . During the past few years, circulating miRNAs have drawn much attention in autoimmune diseases including rheumatic diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Many miRs have been reported to play a critical role in the regulation of many diseased cells, so they have become potential diagnostic or therapeutic targets for a variety of diseases [19,20]. Accumulated studies have reported during the development of RA the abnormal expression of miRs, including miR-155, miR-146a and miR-125 [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%